Arthroscopic treatment for cervical articular process joint osteochondrosis in a Thoroughbred horse. (28th July 2016) - Tucker, R.; Piercy, R. J.; Dixon, J. J.; Muir, C. F.; Smith, K. C.; Potter, K. E.; Leaman, T. R.; Smith, R. K. W.
Summary: A yearling Thoroughbred colt was presented for investigation of neck stiffness and episodes of intermittent neck pain without neurological signs. Osteochondrosis (OCD) of the cervical articular process joints (APJs) was diagnosed with the aid of radiography and computed tomography. An articular osteochondral fragment of the left fourth caudal cervical articular process was removed arthroscopically following a cut down approach to the joint capsule of the affected APJ. Surgical removal resulted in resolution of clinical signs at 4 weeks. However, subsequently the horse was markedly ataxic 6 weeks post surgery after being found cast in its stable. Cervical stenotic myelopathy was considered the most likely cause based on clinical and radiographic signs and the horse was subjected to euthanasia due to a poor prognosis for racing. Post‐mortem examination identified atypical cartilage within several cervical APJs with histological changes consistent with OCD. This case report supports OCD of the APJs as a cause of neck pain and confirms the clinical practicality and short‐term effectiveness of arthroscopic fragment removal. Surgical treatment for cervical OCD should be considered in horses without neurological signs, although case selection is important and the underlying pathology remains a risk factor for the development of subsequent neurological signs.